Performance Allowance, Motivation, Employees’ Work Achievement And Organizational Performance Among Goverment Employees - Muhammad Mudhofar (Magister Ilmu Administrasi Publik, 2021)
This research analyzed the relationships among performance allowance, employee motivation, work achievement and organizational performance in the Ministry of Religion's Office Lumajang City. This research used a quantitative research design based on. Structural Equation Modeling (SEM) model. Research results showed insignificant direct between performance allowance and motivation, employees’ work achievement, and organizational performance. Work achievement has a direct and strongest significant influence on performance improvement in public organizations. Nonetheless, the influence of work achievement on organizational performance is mediated by a number of supporting factors, including performance allowance and motivation.